Improvement of Public Awareness on Fasciolosis as Zoonosis Disease - Martindah, Eny; Widjajanti, S; Estuningsih, S E; ., Suhardono (Indonesian Animal Sciences Society, 2005)
Fasciolosis is commonly suffered by the ruminants such as cattle and buffaloes, and as one of the most important parasitic disease . The prevalence of fasciolosis in ruminants is related to the contaminated feedstuff and water supply with metacercariae, the infective larvae of trematode genus Fasciola spp ., such as Fasciola gigantica and F. hepatica. In Indonesia, the prevalence of this disease in ruminants could be up to 90%, and there is no case report on human being . However, the occurrence of this disease in human should be anticipated, since many cases have been reported in human in the other countries, such as South America, Europe, Australia, New Zealand and South East Asia (Thailand and Vietnam), as